The Medial Collateral Artery is Not Medial - Casey N. Urban, BS; Daniel A. Osei, MD; Scott W. Wolfe, MD (Journal of Hand Surgery Global Online)
Purpose: Current literature interchangeably uses the terms “middle” and “medial” for the middle collateral artery (MCA). However, the term “medial” implies that the artery is positioned on the medial aspect of the arm, which may lead to misunderstandings in medical education or interdisciplinary communication. Our purpose is to provide anatomic and historical support for the use of the original “middle collateral artery” terminology. Methods: We reviewed a 300-year history of anatomy texts to elucidate the origin of the MCA nomenclature. In three cadaveric specimens, the MCA was dissected following latex infusion and its vascular contribution to three pedicled flaps was demonstrated. In three additional specimens, the arms were imaged with computed tomography and three-dimensional reconstruction following barium sulfate infusion. Results: The term “middle” collateral artery predates the term “medial” collateral artery by 80 years. The origin of the term “medial” collateral artery is likely a mistranslation of the predecessor Latin term, “arteria collateralis media.” Our cadaveric dissections and computed tomography imaging confirmed that the MCA’s course is on the posterolateral side of the arm between the anterolateral-positioned radial collateral artery and the medial-positioned superior ulnar collateral artery. Conclusion: The term “medial” collateral artery is an anatomic misnomer. “Middle” collateral artery, its original name, accurately reflects its posterolateral position in the arm between the radial collateral artery and superior ulnar collateral artery. We recommend that authors use the term “middle” collateral artery based on its anatomical position and recommend discontinuation of the term “medial” collateral artery in the scientific literature. Clinical Relevance: Given the MCA’s surgical significance in reconstructive flaps, nonanatomic labeling of the MCA as “medial” may lead to misunderstandings in medical education and surgical site identification. Replacing a misnomer with an anatomically accurate name would improve professional communication and teaching.